THE ENHANCING MATHEMATICS LEARNING OUTCOMES IN MULTIPLICATION FOR GRADE IV STUDENTS THROUGH THE USE OF FINGER CALCULATOR AND TGT METHOD (JOSAR (Journal of Students Academic Research), 2025)
The purpose of this study is to explore how the use of finger calculator and TGT (Teams Games Tournament) can enhance the learning outcomes in multiplication among fourth-grade students at SDN 3 Ringinkembar. This action research follows the model by Kemmis and McTaggart, which includes four stages: planning, implementation, observation, and reflection. To collect data, we used field notes, interviews, quantitative test results, and qualitative observations of both teachers and students. The study was conducted in two cycles with fourth-grade students in May 2019. The reflection stage involved analyzing test results and the application of TGT alongside the finger calculator. The findings indicated that using the finger calculator with the TGT method had positive effects. The students showed increased enthusiasm and improved teamwork, which significantly enhanced their learning outcomes in multiplication. The completion rate rose from 45% to 85% after implementing finger calculator and TGT, demonstrating the effectiveness of these methods in improving the students' understanding and mathematical performance.